Modelling the impact of tidal flows on the biological productivity of the Alboran Sea - Sánchez-Garrido, José Carlos; Naranjo-Rosa, Cristina Belén; Macías, Diego; García-Lafuente, Jesús; Oguz, Temel (My University, 2015)
The control of phytoplankton production by tidal forcing in the Alboran Sea is investigated with a three-dimensional circulation model coupled to an ecosystem model. The aim of the modeling efforts was to elucidate the role of tides in sustaining the high biological productivity of the Alboran Sea, as compared with the rest of the Mediterranean. Model results indicate that tides have a strong impact on the biology of the western half of the basin, where primary productivity increases by a factor of 3/2 with respect to a non-tidal simulation. The likely physical processes for these discrepancies are investigated and discussed, including internal tides, tidal mixing occurring in the Strait of Gibraltar, and ageostrophic flows originating from the strait's lateral boundary layers. It is argued that the nutrient enrichment of the Atlantic inflow caused by mixing at the Strait Gibraltar accounts for nearly all the tidally driven increase of primary productivity.
Keywords: Productividad primaria (Biología) -- Medición; Ocean Modelling; Tides; Physical-Biological Interactions; Primary Productivity